Dropwise Condensation on Inclined Textured Surfaces - Khandekar, Sameer; Muralidhar, Krishnamurthy; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Dropwise Condensation on Textured Surfaces presents a holistic framework for understanding dropwise condensation through mathematical modeling and meaningful experiments. The book presents a review of the subject required to build up models as well as to design experiments. Emphasis is placed on the effect of physical and chemical texturing and their effect on the bulk transport phenomena. Application of the model to metal vapor condensation is of special interest. The unique behavior of liquid metals, with their low Prandtl number and high surface tension, is also discussed. The model predicts instantaneous drop size distribution for a given level of substrate subcooling and derives local as well as spatio-temporally averaged heat transfer rates and wall shear stress.
Introduction -- Modeling Dropwise Condensation -- Dropwise Condensation: Simulation Results -- Dropwise Condensation: Experiments -- Concluding remarks and perspectives.
Keywords: Engineering; Hydraulic engineering; Surfaces (Physics).; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Surfaces and Interfaces, Thin Films; Engineering Fluid Dynamics